Type 1 equilibrative nucleoside transporter (ENT1) regulates sex‐specific ethanol drinking during disruption of circadian rhythms. (2nd July 2019) - Jia, Yun‐Fang; Vadnie, Chelsea A.; Ho, Ada Man‐Choi; Peyton, Lee; Veldic, Marin; Wininger, Katheryn; Matveyenko, Aleksey; Choi, Doo‐Sup
Abstract: Disruptions in circadian rhythms are risk factors for excessive alcohol drinking. The ethanol‐sensitive adenosine equilibrative nucleoside transporter type 1 (ENT1, slc29a1 ) regulates ethanol‐related behaviors, sleep, and entrainment of circadian rhythms. However, the mechanism underlying the increased ethanol consumption in ENT1 knockout (KO) mice in constant light (LL) and whether there are sex differences in ethanol consumption in ENT1 mice are less studied. Here, we investigated the effects of loss of ENT1, LL, and sex on ethanol drinking using two‐bottle choice. In addition, we monitored the locomotor activity rhythms. We found that LL increased ethanol drinking and reduced accumbal ENT1 expression and adenosine levels in male but not female mice, compared with control mice. Interestingly, only LL‐exposed male, not female, ENT1 KO mice exhibited higher ethanol drinking and a longer circadian period with a higher amplitude compared with wild‐type (WT) mice. Furthermore, viral‐mediated rescue of ENT1 expression in the NAc of ENT1 KO mice reduced ethanol drinking, demonstrating a possible causal link between ENT1 expression and ethanol drinking in males. Together, our findings indicate that deficiency of ENT1 expression contributes to excessive ethanol drinking in a sex‐dependent manner. Abstract : We demonstrated that constant light (LL) increased ethanol drinking and reduced accumbal ENT1 expression and adenosine levels in male but not female mice. Additionally, LL‐exposed male ENT1 KO mice specifically exhibited higher ethanol drinking and longer circadian period. Our findings indicate that deficiency of ENT1 contributes to excessive ethanol drinking in a sex‐dependent manner.